PEMANFAATAN MASSIVE OPEN ONLINE COURSES DALAM PEMBELAJARAN AL QUR’AN DI ERA DIGITAL - Rokhim, Ahmad Abdur; Rusydiyah, Evi Fatimatur (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
This article aims to discuss the use of Massive Open Online Course (MOOC) media in learning the Qur'an in the digital era. The research method used in this study is a descriptive qualitative approach. In the current era, technological developments have brought the world of education to think about issuing learning innovations that are ready to meet the demands of the times. This includes online-based open courses or commonly referred to as Massive Open Online Courses (MOOC). The success of several MOOC platforms in providing various courses, such as English, Mathematics, Management, Physics, Graphic Design and so on is read as an opportunity also to develop online and open learning of the Qur'an. The use of MOOC media will be able to accommodate a large number of participants from various regions. This opportunity was then responded by several educational institutions to provide an online and open Qur'an learning platform, such as the Intensive Tahfidz, Griya Al Qur'an, Baitul Qur'an Daarul Qur'an, Tahsin Online Academy, and Qur'an Edu Center.